THU0423 ANTERIOR TIBIOTALAR FAT PAD MORPHOLOGY AND SIGNAL INTENSITY ON MAGNETIC RESONANCE IMAGING ARE CORRELATED WITH PATIENT CHARACTERISTICS AND JOINT PATHOLOGY. (June 2019) - Arnaert, Stijn; Byttebier, Paul; Rossom, Sam Van; Vereecke, Evie; Jonkers, Ilse; Oei, Edwin; Bierma-Zeinstra, S.M.A.; Lories, Rik; Middelkoop, Marienke Van; Clockaerts, Stefan
Abstract : Background: Ankle sprains are the most frequent form of trauma in the ankle and up to 33% of patients experience ongoing pain 1 year after the initial trauma. 1 In the ankle, trauma is the primary etiology of osteoarthritis with an overwhelming proportion of 70-78%. 2 Recently, our group completed a small pilot study that suggested that the anterior tibiotalar fat pad (ATFP) should be investigated as a source of inflammation and pain. 3 Objectives: In this study, we tried to investigate the innovative concept of the ATFP as missing link in the pathogenesis of persistent complaints and potential source driving inflammation in the development of osteoarthritis. Methods: The present study is a secondary analysis of an observational case control study by Van Ochten et al. 4 We included 106 patients with a Kellgren & Lawrence score of 0 in the tibiotalar joint on x-ray. T1 MRI scans were assessed for the signal intensity and area of the ATFP by mapping the fat pad in 'Mimics 18.0'. After importing those mapped scans in the program 'MATHLAB', quantitative values of intensity and area were generated. Those values were statistically tested for correlations with patient characteristics and structural abnormalities by univariate and multivariate linear regression. Results: MRI signal intensity of the ATFP is associated with BMI (p= 0.03), sex (p<0.01) and age (p= 0.01). ATFP area is correlated with sex (p<0.01) and presence of pre-OA signs in the subtalar joint (p= 0.01). After multivariate analysis, correcting for sex, subtalar pre-OA signs and BMI, persistent complaints were associated with ATFP area (p= 0.04). Conclusion: This study demonstrates the involvement of the ATFP in hindfoot joint pathology. ATFP MRI characteristics were also influenced by patient characteristics. Further research should confirm these findings in a more elaborate population including OA patients, focus on histological validation and determine underlying pathogenic processes that may explain the observed correlations. References: [1] van Rijn, R. M. et al. What Is the Clinical Course of Acute Ankle Sprains? A Systematic Literature Review. American Journal of Medicine 121, (2008). [2] Valderrabano, V., Horisberger, M., Russell, I., Dougall, H. & Hintermann, B. Etiology of ankle osteoarthritis. Clinical Orthopaedics and Related Research 467, 1800–1806 (2009). [3] Clockaerts, S. et al. The anterior tibiotalar fat pad as a source of pain and inflammation in osteoarthritis of the ankle: anatomy, histology and imaging. Osteoarthr. Cartil. 26, S120 (2018). [4] Van Ochten, J. M. et al. Structural abnormalities and persistent complaints after an ankle sprain are not associated: An observational case control study in primary care. Br. J. Gen. Pract. 64, e545–e553 (2014). Disclosure of Interests: Stijn Arnaert: None declared, Paul Byttebier: None declared, Sam Van Rossom: None declared, Evie Vereecke: None declared, Ilse Jonkers: None declared, Edwin Oei: None declared, S.M.A. Bierma-Zeinstra: None declared, Rik Lories Consultant for: Abbvie, Celgene, Eli-Lilly, Janssen, Merck, Novartis, Pfizer, UCB, Marienke Van Middelkoop: None declared, Stefan Clockaerts: None declared